Survey of Holt Adoptees and Their Families, 2005 - Sacerdote, Bruce ([Verlag nicht ermittelbar], 2007)
This study, conducted January 2004 to June 2006, was undertaken to assess the health status, educational attainment, and income of adult Korean-American adoptees and their adoptive families. The study focused on families who adopted a Korean-American child through Holt International Children's Services from 1970 to 1980. The principal investigator hoped to identify the effects of large-scale changes in family environment on children's outcomes using data on adults who were adopted in infancy. Korean-American adoptees placed through Holt International Children's Services had been quasi-randomly assigned to these families in infancy using a queuing (first-come, first-served) policy. One adoptive parent from each family was surveyed, as well as a small subset of adult adoptees, and each case represented an adopted or non-adopted child in the family. Adoptive parents were asked to give their age, sex, marital status, occupation, education level, household income, height, weight, tobacco and alcohol usage, and the number of children they had. Adoptive parents also gave information on their adopted and non-adopted children's age, sex, marital status, education level, income, weight, height, undergraduate institution, number of children, and whether their children smoked, drank alcohol, or had asthma. For adopted children, parents gave the arrival age of the child and whether the child was adopted through Holt International. Adoptive parents also indicated whether they were aware of and had used services such as workshops and referral services offered by Holt. Since the survey relied on parent reports of their adult children's outcomes, surveys were also sent to a small subset of adoptees. Their surveys included the same questions asked of their adoptive parents, as well as the adoptee's value of assets, religion, and frequency of religious attendance. The study also contained information on adoptees' birth parents obtained from Holt International's administrative records and constructed variables that analyzed household composition, population characteristics, and the education and health status of the adoptive family.